Developing TBLT-Based Digital Storybook For 9th-Grade Students at SMP Negeri 4 Singaraja - Kadek Shinta Fridayanti; I Putu Ngurah Wage Myartawan; Ni Putu Astiti Pratiwi (Acitya: Journal of Teaching and Education, 2023)
This study aims to develop TBLT-based digital storybook to facilitate students’ literacy activities for 9th-grade students at SMP Negeri 4 Singaraja. This research uses the Design and Development model by Richey and Klein (2014) as the basis of the methodology. Design and Development model has four stages, namely analysis, design, development, and evaluation. The data obtained from this study used instruments in the form of questionnaires, interviews, observations, and document analysis. The quality of TBLT-based digital storybook product received excellent product from two experts, and this product is valid to be applied in learning activities to facilitate literacy activities for 9th-grade students. The application of TBLT-based digital storybook was carried out through trial by small group as a formative assessment and get good responses from the teacher and students. The results of this study concluded that digital storybook-based TBLT with "Narrative Text" material for grade 9 students can help students to facilitate their English skills because it contains tasks according to the stages of TBLT which focus on developing students’ English skills. In addition, this digital storybook also helps the teacher in determining learning media that are innovative and can motivate students in learning activities.